Cyber-Biosecurity Risk Perceptions in the Biotech Sector - Millett, Kathryn; dos Santos, Eduardo; Millett, Piers D. (Frontiers in Bioengineering and Biotechnology, 2019)
The expanding digitization of the biological sciences places greater value on the data generated, information extrapolated and knowledge gained. Failing to protect data will affect a company or country’s ability to position itself optimally in the forthcoming fourth industrial revolution. Further, more reliance on automation, distribution and outsourcing in biotechnology makes its infrastructure a target. The equipment and service providers that drive physical research and development are also all connected online. Failing to protect these resources from intrusion increases the risk of accidental or deliberate harm, for example by the loss of control over biological products. Robust cybersecurity measures are therefore critical for both securing the data generated by the biotechnology sector as well as securing key infrastructure. Cyber-biosecurity is emerging multidisciplinary field that combines cybersecurity, biosecurity and cyber-physical security as relates to biological systems. To better identify the perceived risks at the interface between cybersecurity and biosecurity, Biosecure conducted a pilot study surveying the views of a discrete set of biotechnology and cybersecurity leaders. The survey was carried out online from October-November 2017. Key findings of the survey showed that cyber-biosecurity risks were considered to be difficult to characterize due to variations in types of threats, targets and potential impacts, and compounded by a notable variation between the level of sophistication or maturity of mitigation and response measures. Further research is therefore necessary bringing together the different communities focusing on these issues to develop a common language, better define the threats and discuss potential ways forward in addressing risks.